Selling Internet Gambling: Advertising, New Media and the Content of Poker Promotion. - McMullan, John; Kervin, Melissa (International Journal of Mental Health & Addiction, 2012)
This study examines the web design and engineering, advertising and marketing, and pedagogical features present at a random sample of 71 international poker sites obtained from the Casino City directory in the summer of 2009. We coded for 22 variables related to access, appeal, player protection, customer services, on-site security, use of images, text, and language, interactive and immersive materials, promotional products and programs, sponsorships, celebrities, tutelage resources, responsible gambling programs, and thematic content. We explore several questions: How are Internet poker sites designed and stylized to create trust and familiarity and attract and retain consumers? How prevalent are the new forms of social media such as 'viral marketing,' 'network marketing,' and 'word of mouse' advertising in reaching and constituting poker players as consumers? What mechanisms do internet gambling websites deploy to socialize customers to purchase their products and enter into a culture of poker? What are the master advertising messages at websites and what are their implications for responsible gambling and problem gambling?